Key Determinant Factors of Firm Value for Energy Sector Companies - Marsella Dyah; Lenni Yovita; Herry Subagyo; Vicky Oktavia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The aim of this research is to analyze the determinant factors of Firm Value in Energy Sector Companies listed on IDX 2020-2023. the variable selected in this study were profitability, capital structure and firm size as an independent variable, and Firm Value as a dependent variable. data collection techniques use the purposive sampling method. using secondary data obtained from financial reports on IDX from 2020-2023 with a total of 34 companies. based on the result of the tests prove that profitability has positive significant effect on Firm value, Capital Structure has A significant effect on Firm value, and Firm Size has a positive significance effect o Firm Value. By bridging these concepts, this research explores a deeper understanding of how profitability, capital structure, and company size can have a positive impact on company value. The findings of this research have significant implications for financial management in determining the amount of company value by taking into account profitability, capital structure and company size in investment decisions.